Beatrice doesn't want to - Numeroff, Laura Joffe; Munsinger, Lynn (Cambridge, Mass. : Candlewick Press, 2004)
On the third afternoon of going to the library with her brother Henry, Beatrice finally finds something she enjoys doing.
Keywords: Libraries -- Fiction; Brothers and sisters -- Fiction; Libraries -- Juvenile fiction; Siblings -- Juvenile fiction